Additions to the Estonian fauna of mycophagous Cecidomyiidae (Diptera), with a description of Unicornella estonensis gen. et sp. nov. - Sikora, Tomáš; Jaschhof, Mathias; Kurina, Olavi (Zootaxa, 2020)
Mycophagous gall midges from two Malaise trapping campaigns in Estonia were subjected to a morpho-taxonomic study, with the aim of identifying previously unrecorded species. Fifty-four species are shown for the first time to occur in Estonia, specifically 1 Lestremiinae, 21 Micromyinae, 5 Winnertziinae, and 27 Porricondylinae. This raises the number of mycophagous cecidomyiids known from Estonia to 152, which is about one fourth of the total estimated for the national fauna. One of the Porricondylinae turned out to be new to science and is described as Unicornella estonensis Jaschhof & Sikora. Unicornella, a new genus of the tribe Porricondylini, is characterized by that males have a single gonocoxal process, as opposed to two or no processes found in other Porricondylini.